Educational software for stress analysis of idealized thin walled open sections - Syed Mohamed Ali, Jaffar; ., Hasna Nur Fadhila; Aziz, Nor Azhanadia (Trans Tech Publications Ltd., Switzerland, 2013)
An educational software which can aid students in stress analysis of idealized thin-walled open sections has been developed. The software enables students to select different cross-sections which may be subjected to bending, shear or torsional loads and evaluate the stresses on it. Results obtained through this software have been validated. The software has been developed using MATLAB with graphical user interface (GUI). The software is expected to be a useful tool for effective teaching learning process of courses on thin-walled structures and aircraft structures.